Criminals and Victims. - Allen, W. David (Stanford University Press, 2011)
Criminals and Victims presents an economic analysis of decisions made by criminals and victims of crime before, during, and after a crime or victimization occurs. Its main purpose is to illustrate how the application of analytical tools from economics can help us to understand the causes and consequences of criminal and victim choices, aiding efforts to deter or reduce the consequences of crime. By examining these decisions along a logical timeline over which crimes take place, we can begin to think more clearly about how policy effects change when it is targeted at specific decisions within.